Sweden : Financial Sector Assessment Program-Technical Note-Insurance Sector Regulation and Supervision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program (FSAP) for Sweden in the areas of insurance sector regulation and supervision. The regulatory and supervisory framework has been enhanced since the 2011 FSAP. The Finansinspektionen (Financial Supervisory Authority, FI) is the principal regulatory body, with responsibility for prudential regulation, consumer protection, and macroprudential regulation. Some measures are recommended to strengthen solvency regulation further. Solvency II should be applied in full to occupational pensions insurance, unless the government decides to create a separate national regime for occupational pensions, as exists in many other countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet